Measurement of rill erosion through a new UAV-GIS methodology - Bazzoffi, Paolo (Italian Journal of Agronomy, 2015)
Photogrammetry from aerial pictures acquired through micro Unmanned Aerial Vehicles (UAV), integrated by post-processing is a promising methodology both in terms of speed of data acquisition, degree of automation of data processing and cost-effectiveness. The new UAV-GIS methodology has been developed for three main purposes: i) for a quick measurement of rill erosion at a field scale with the aim of combining the simplicity of field survey to reliability of results, at an affordable price; ii) to calibrate the RUSLE model to make it suitable for the purposes of the CAP common indicator; iii) to provide an easy evaluation tool to Regions and to non-research professionals who use the very popular ESRI ArcGis software for assessing the effectiveness of soil conservation measures adopted under CAP and to calibrate the common indicator â€œsoil erosion by waterâ€. High-resolution stereo photos pairs, acquired close to the soil, are of crucial importance in order to produce high resolution DEMs to be analysed under GIS. The GIS methodology consists of the measurement of rill erosion that occurred in a plot from the total volume of the incisions, regardless of internal sediment redeposition, based on Plan Curvature analysis and Focal Statistics analysis, described in detail, as they are the essential constituents of the new methodology. To determine the effectiveness and reliability of the new methodology a comparison between rill depth measured manually on field of 51 rill points and depth measured by UAV-GIS methodology was done. The best calibration equation was obtained by using 30 cm radius in the Focal statistics analysis. The linear regression equation resulted highly significant with R2 =0.87. Two case studies are presented, solved step by step, in order to help the user to overcome possible difficulties of interpretation in the application of the GIS procedure. The first solved exercise concerns a heavily eroded plot where only one DEM, derived from post erosion UAV photos, was used to calculate rills erosion. In this case, incisions due to tillage tools and wheel tracks (false rills) which were present on the soil surface before soil erosion had occurred were no longer present at flight time, as they have been fully incorporated (absorbed) by rills. The second exercise concerns a less rilled plot, where the diachronic analysis of DEMs was deemed necessary to subtract from the rill volume the false rill volume which was still present on the soil surface before soil erosion has occurred. In this case rill erosion increased the volume of preexisting mechanical incisions that are still distinguishable (with the naked eye on the field) from the incision forms due to runoff water. A solved exercise to assess interrill erosion from the calculated value of rill erosion, according to a previous study of 1989, is also reported. A comparison between UAV-GIS measured and RUSLE predicted erosion rates is also reported, which gives a first confirmation of validity of the new methodology.